CONTINUATION OF ACADEMIC STUDIES AND SPORTS ACHIEVEMENT GRADUATES OF THE TALENTED SPECIAL CLASS IN SPORTS: A CASE STUDY - Duwi Kurnianto Pambudi; Sumaryanto Sumaryanto; Guntur Guntur (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
Academic learning and sports coaching are things that must be done by Sports Class (KKO SMA) students. Specific and well-planned training, coaching, competition and recovery will ensure optimal development throughout an athlete's career. Academic paths, self-development, and continuing studies from high school to university are factors in preparing for the future. so that academic education and sports skills development must be synergistic. The method used in the research was descriptive with the instrument being a questionnaire adapted from Renzully's three ring prize concept which was tested for validity and reliability on 20 respondents with Cronbach's Alpha with a result of 0.79. so that the results of interest in majors at KKO High School show KKO (M = 4.596, SD = 0.754), Learning and training process (M = 2.662, SD = 0.816), so it can be concluded that school and training schedules are the two lowest items, need to be given attention and special treatment to be scheduled in an organized manner so that training and education can complement each other and be synergistic.